The Effectiveness of Audiovisual-Based Reproductive Health Education in Preventing Risky Sexual Behavior Among Junior High School Adolescents in Urban Communities - Jetty Mongdong; Kartini Estelita Tungka; Jolie Febri Ponamon (Open Access Health Scientific Journal, 2026)
Background: Adolescence is a transitional period from childhood to adulthood characterized by psychological instability and increased susceptibility to negative influences when adequate supervision and education are lacking. Inadequate reproductive health knowledge may increase the likelihood of engaging in risky sexual behaviors. This study aimed to analyze the effect of reproductive health education delivered through audiovisual media on the prevention of risky sexual behavior among junior high school adolescents in urban areas. Methods: A quantitative study with a pre-experimental one-group pretest-posttest design was conducted among 33 junior high school students. Data were collected using a questionnaire assessing efforts to prevent risky sexual behavior. Participants received reproductive health education through audiovisual media. Data were analyzed using the Wilcoxon signed-rank test. Results: Among the participants, most were 13 years old (63.6%), Christian (63.6%), and had two siblings (48.5%). Before the intervention, 66.7% of respondents demonstrated a moderate level of risky sexual behavior prevention efforts, while 33.3% were categorized as poor. After the intervention, 81.8% of respondents achieved a good level of prevention efforts and 18.2% remained in the moderate category. The Wilcoxon signed-rank test showed a statistically significant improvement in prevention efforts following the intervention (Z = -4.916, p < 0.001) Conclusion: Reproductive health education delivered through audiovisual media significantly improved the prevention of risky sexual behavior among junior high school adolescents in urban areas. Audiovisual media can be considered an effective educational approach for promoting reproductive health awareness and preventive behaviors among adolescents.